إنعكاسات النفعية والتسليع على البحث العلمي: دراسة تقييمية من منظور التربية الإسلامية - الحارثي، عبدالرحمن محمد نفيز المذاهبي (جامعة الأندلس للعلوم والتقنية, 2022)
هدفت الدراسة إلى: توضيح انعكاسات النفعية على البحث العلمي، وبيان منظور التربية الإسلامية للنفعية في البحث العلمي، وتوضيح انعكاسات التسليع على البحث العلمي، وبيان منظور التربية الإسلامية للتسليع في البحث العلمي، أوضحت النتائج أن النفعيين يتفقون على أن المنفعة هي غاية الخير والأخلاق، فالصدق أو نفي الكذب ليست هي الغاية؛ بل الغاية ما يترتب عليها من نتائج والتي هي في نهاية الأمر منفعة مادية محسوسة، وأن المنفعة في الإسلام قد تكون دنيوية مادية، وقد تكون أخروية، وقد تجمع بين الأمرين بمنهجية قانونية متوازنة تراعى فيها المصلحة العامة والمصلحة الخاصة، وأن من انعكاسات النفعية على البحث العلمي إضعاف الإبداع عند العقل الإسلامي، وانعزاله عن سياقه الاجتماعي أثناء النظر للمشكلات التي يتناولها في البحث العلمي، ومن انعكاسات فكرة التسليع على البحث العلمي أن الإنسان يتحول إلى "شيء" فلا تتجاوز نظرته في العلوم السطح المادي وعالم الأشياء، وذلك لأنه يسير وفق نماذج محددة بسيطة، كما لو أنه يتعامل مع المادة ذاتها. This study aimed to: Clarify the implications of utilitarianism on educational research, clarify the Islamic perspective on utilitarianism in educational research, clarify the implications of commodification on educational research, and clarify the Islamic perspective on commodification in educational research. The results showed that utilitarians agree that utility is the end of morals. Truth or denial of lies is not the end; Rather, the end is what results from it, which is ultimately a tangible material benefit, and that the benefit in Islam may be materialistic, and it may be hereafter, and it may combine the two things with a balanced legal methodology that takes into account the public and the private interests, and that one of the repercussions of utilitarianism on educational research is weakening creativity in the Islamic mind, and its isolation from its social context while looking at the problems it deals with in educational research, and one of the repercussions of the idea of commodification on educational research is that man turns into a ''thing'' so his view of science does not go beyond the material surface and the world of things, because it follows simple specific models, as if dealing with the same substance.
Keywords: البحوث التربوية -- التربية الأخلاقية -- الفكر الإسلامي -- فلسفة النفعية -- سياسات التسليع